Harnessing electricity retail tariffs to support climate change policy - Lisa Ryan; Sarah La Monaca; Linda Mastrandrea; Petr Spodniak (University College Dublin, UCD School of Economics, 2018)
Legacy electricity retail tariffs are ill-adapted to future electricity systems and markets, particularly with regard to accommodating the multi-faceted shift toward decarbonisation. We examine how retail tariffs need to be reformed to not only meet the future revenue requirements of energy-suppliers and networks but also to help achieve the environmental objectives of the energy transition. While existing literature has explored the link between retail tariff structure design, wholesale markets and/or network cost recovery, there is less recognition of the impact of tariff structure design on environmental objectives. This paper reviews the demand responsiveness of household customers to electricity prices and implications of retail tariff structure and design for the policy targets of CO2 emissions, energy efficiency, and renewable electricity generation, in addition to electricity system. A review of the literature provides a theoretical basis for price elasticity of demand and electricity retail tariff design, and we explore the environmental implications for future retail tariff design options via examples of various tariff structures in the EU and US. The research links the topics of emissions mitigation policy and market design, and should add empirical insights to the body of academic literature on future electricity markets. It should also be of interest to policy makers wishing to consider retail tariff structures that promote decarbonisation of the electricity system through multiple objectives of improved energy efficiency and increased shares of renewable electricity within future electricity markets.
Keywords: H2; Q21; Q41; Q42; 330; electricity retail tariffs; electricity prices; energy policy; decarbonisation of electricity